A simple assessment of haemothoraces thickness predicts abundant transfusion: A series of 525 blunt trauma patients. Issue 1 (January 2015) - Gignon, Lucile; Charbit, Jonathan; Maury, Camille; Latry, Pascal; Taourel, Patrice; Millet, Ingrid; Capdevila, Xavier
Abstract Background The goal of this study was to evaluate the performance of haemothorax quantification to predict an abundant transfusion in blunt thoracic trauma patients. Methods This study included all severe trauma patients admitted into our trauma centre from January 2005 to January 2010, who presented a blunt thoracic trauma (thoracic AIS ≥1) and had a CT scan within the first hour following admission. For each haemothorax, thickness of dominant side and the cumulated thicknesses of both sides (Dominant-t, Cumulated-t), as well as lengths (Dominant-l, Cumulated-l) and the calculated volumes (Dominant-v, Cumulated-v provided by a previously validated formula) were retrospectively measured by CT scan. A multiple logistic regression was performed to define the independent risk factors for an abundant transfusion (≥5 packed red blood cells in the first 24 h). Finally, ROC curves have been drawn on an isolated thoracic trauma subgroup to predict abundant transfusion. The more specific cut-offs were extracted from this analysis. Results From the 525 blunt thoracic trauma patients (75% males, mean age 38.2 (SD18.7) years, mean ISS 22.5 (SD16.4)), 31% received an abundant transfusion. In multivariable analysis, Cumulated-t was significantly associated with an abundant transfusion (OR 1.3 [95% CI 1.1–1.4], P = 0.002). In isolated thoracic trauma subgroup (n = 251), the global abilities of different CT measurements to predict abundant transfusion were significantly comparable (AUCs 0.69–0.70). The more specific cut-offs were established at 28 mm for Cumulated-t (specificity 92%, positive predictive value 47%) and at 24 mm for Dominant-t (specificity 92%; positive predictive value 43%). Conclusion The haemothorax quantification upon admission may help to predict transfusion needs. Cumulated-t was found independent risk factor for abundant transfusion in a large population of severe trauma patients. Beyond a Cumulated-t of 28 mm or a Dominant-t of 24 mm, abundant transfusion will be very frequently necessary. Level of evidence Retrospective review, level III.